(untitled) (Agroindustria, Sociedad y Ambiente, 2025)
Bougainvillea flowers stand out for their different functional properties within the food and non-food industry. The objective of the research was to evaluate the physicochemical, antioxidant and sensory properties of Bougainvillea glabra. A completely randomized experimental design was used, consisting of 4 treatments where 4 concentrations (1; 7.5; 15 and 30 g) of bougainvillea flower were evaluated. A physicochemical characterization of the bougainvillea flower and antioxidant capacity, phenolic, microbiological and sensory content of the bougainvillea infusion was carried out. The results of the physicochemical characterization of bougainvillea flower showed a moisture content of 77.03%, dry matter 22.98%, ash 2.19%, antioxidant activity 98.58 µmol Trolox Equivalent/ g flower by ABTS and 92.79 µmol Trolox Equivalent/ g flower by DPPH. The antioxidant evaluation showed that the T4 treatment was superior with 603.39 µmol Trolox equivalent/ 100mL by ABTS and 525.77 µmol Trolox equivalent/ 100mL. The phenolic content was higher in the T4 treatment with 205.45 mg GAE/100mL infusion. Microbiological analysis showed the absence of E. coli, Clostridium sulfite reducers and Salmonella complying with the criteria of the NTE INEN 2392:2017 standard. The sensory evaluation identified significant differences between the samples finding a better acceptance in the T4 treatment in the attributes color (3.84), odor (3.50), flavor (3.76) and general appearance (3.73). It is concluded that the inclusion of 30 g of flower per 100 mL of water improved the chemical and sensory profile.